Pancreatic Protection Effects of Butterfly Pea (Clitoria Ternatea) Flower Extract Against White Rattus Novergicus Induced By Alloxan - Farid Fani Temarwut; Suprapto Prayitno; Saenal Edi Kamal; Skolastika Biana Sari; Evi Ayu Hartanti (Universitas Pakuan, 2023)
The pancreas is an endocrine gland that produces the peptide hormones insulin, glucagon, and somatostatin, and also an exocrine gland that produces digestive enzymes. These hormones play an important role in regulating the body's metabolic activities, especially blood glucose homeostasis. The aim of this study was to investigate the ethanolic extract of butterfly pea flower (Clitoria ternatea L) against white rats (Rattus novergicus) induced by alloxan and to I the level of its damage. Fifteen male wistar rats (150-200 g) body weight (BW) were divided into 5 groups. The control healthy group, the placebo group and the extract treated group that received 150 mg/kg BW (group I), 300 mg/kg BW (group II) and 450 mg/kg BW (group III) orally. Placebo (Na-CMC) and extract were given for 5 consecutive days before alloxan administration (150 mg/kg BW) on days 6 and 7. Blood samples were taken to determine the glucose and albumin levels on day 0 (before treatment), on day 5 (after treatment of the extract but before the administration of alloxan), and on 6 and 7 after 24 h administration of alloxan. Alloxan induced gives a significant increase in glucose and albumin levels. The average of glucose level was 236.6±37.6 mg/dl in the health control, 252±28.1 mg/dl in the placebo group, 137±35.5 mg/dl in the extract of group I, 115.9±19.1 mg/dl in the extract of 300 mg of group II and 145.2±58.6 mg/dl of group III. Meanwhile the average of albumin level in the healthy group was 3.39±0.8 g/dl, the placebo group was 2.7±0.2 g/dl, the group I was 1.9±0.04 g/dl, the group II was 1.77±0.16 g/dl, and the group III was 1.85±0.19 g/dl. This study showed that at highest dose of C. ternatea was able to significantly prevent the elevation pancreatic damage biomarkers and this finding was associated with the result of histopathological analysis of the pancreas. These results suggest that the ethanol extract of C. ternatea at a dose of 450 mg/kg BW (group III) has a good protective effect on the function and structure of pancreatic tissue.